Synthesis, characterization and cytotoxicity of Chitosan/Polyvinyl Alcohol/Bioactive Glass hybrid scaffolds obtained by lyophilization - Silva,Alexandra Rodrigues Pereira da (2016)
ABSTRACT One of the important research topics in tissue engineering is the development of optimum three-dimensional scaffolds for regeneration and growth of bone tissue. The scaffold developed should promote an initial biomechanical support, provide the formation, deposition and organization of the new organic matrix generated, and degrade proportionally to the growth of the new tissue. In this study hybrid scaffolds based on the blend Chitosan (CHI)/Poly (vinyl alcohol) (PVA), with two different CHI:PVA molar ratios (1:1, and 3:1), and Bioactive Glass as the inorganic phase, were developed by a sol-gel route, followed by lyophilization. The materials were cross-linked with Glutaraldehyde. The obtained porous scaffolds were characterized by SEM, FTIR, porosity measurements by Archimedes method, and compression test. The in vitro degradation was studied by immersion in simulated body fluid for several time periods and evaluation of mass loss. Citotoxicity analysis was carried out on samples as prepared and after immersion in PBS solution for 24hrs, using human fibroblast cells and MTT method to evaluate cell viability. The matrices obtained showed promising results, presenting about 96% porosity, pore size varying in the range 20-300 µm, and interconnected pores. The mass loss presented by the matrices with CHI/PVA ratios 3:1 and 1:1 during the degradation test in vitro, was around 10% after a week of testing, with macroscopic preservation of their physical structure. Cytotoxicity tests showed that the samples were toxic as produced and not toxic after treatment with PBS, showing this approach was suitable as a final preparation step of these samples.